Tradisi Meurukon dalam Masyarakat Muara Batu Aceh Utara: Sebuah Kajian Sosial Budaya dan Pesan Teologi - Lukman Hakim; Nella Fitria; Musdawati Musdawati (Program Studi Aqidah dan Filsafat Islam, 2021)
Meurukon is a religious tradition that still exists and develops in Acehnese society. This tradition is used as a means of religious education for teenagers in Aceh. This meurukon tradition includes: theology, Islamic law and Sufism. This article examines theological values in the meurukon tradition that is practiced in the Muara Batu community, North Aceh. Data obtained through observation, in-depth interviews and documentation. The data obtained were analyzed using descriptive analysis method. This study concludes, First, the Merukon tradition is described as a religious tradition that is manifested in poetry or nazam which is carried out in groups and led by a chief (shaikh). This activity is carried out in a dialogical way (sue-eu, jaweub) in which the chairperson questions a certain problem, which is then answered together by group members. Second, the main material contained in this meurukon tradition is a matter of faith or theology. The discussion related to this theology covers several aspects, such as about the nature of Allah and the messengers, both obligatory, impossible and jaiz, as well as about angels, books and the afterlife. This tradition is known as a cultural heritage that contains educational values in the Tauhid education among the Acehnese people.